Evaluation of Time Dependent Performance of the 2 nd Year Libyan Dental Students - Elkadiki, Nuha; Aldebaibiabg, Yousef; Alawjali, Samia; Greiw, Azza; Bubtaina, Najat; Betamar, Naeima (Libyan Journal of Dentistry, 2018)
Objectives: To evaluate and compare the academic performance of the second year dental students in the preclinical laboratory periods at three different session-times. Materials and Methods: This study was carried out enrolling all second year dental students (n=267) at the Department of Conservative Dentistry and Endodontic, Faculty of Dentistry, University of Benghazi. The data were collected using the evaluation of students at preclinical laboratory sessions throughout the academic year, in addition to self-administered questionnaires to evaluate factors affecting performance of students. Each student was evaluated by performing a class I cavity preparation and amalgam restoration on a first mandibular left molar of a mounted (Typodont) tooth. The score obtained using a grade from 1-10 at three different session-times; early (8-10 am), mid-day (10-12 am), and late (12-2 pm) session. Data were statistically analyzed using One-way ANOVA and Tukey’s post-hoc test using SPSS version 16. Results: Statistical analysis showed a significant difference between student’s scores attending mid-day and early sessions in class I cavity preparation, their means were 7.61 ± 0.77 and 7.25 ± 0.77 respectively (P=0.005). A significant difference was also observed between late and early sessions (7.54 ± 0.80 and 7.25 ± 0.77) respectively (P=0.059). Regarding class I amalgam restoration, there was a significant difference between student’s scores attending mid-day and early sessions, their means were 7.80 ± 0.62 and 7.53 ± 0.59 Objectives: To evaluate and compare the academic performance of the second year dental students in the preclinical laboratory periods at three different session-times. Materials and Methods: This study was carried out enrolling all second year dental students (n=267) at the Department of Conservative Dentistry and Endodontic, Faculty of Dentistry, University of Benghazi. The data were collected using the evaluation of students at preclinical laboratory sessions throughout the academic year, in addition to self-administered questionnaires to evaluate factors affecting performance of students. Each student was evaluated by performing a class I cavity preparation and amalgam restoration on a first mandibular left molar of a mounted (Typodont) tooth. The score obtained using a grade from 1-10 at three different session-times; early (8-10 am), mid-day (10-12 am), and late (12-2 pm) session. Data were statistically analyzed using One-way ANOVA and Tukey’s post-hoc test using SPSS version 16. Results: Statistical analysis showed a significant difference between student’s scores attending mid-day and early sessions in class I cavity preparation, their means were 7.61 ± 0.77 and 7.25 ± 0.77 respectively (P=0.005). A significant difference was also observed between late and early sessions (7.54 ± 0.80 and 7.25 ± 0.77) respectively (P=0.059). Regarding class I amalgam restoration, there was a significant difference between student’s scores attending mid-day and early sessions, their means were 7.80 ± 0.62 and 7.53 ± 0.59 respectively (P=0.005). Conclusion: Early session has the least score performance among the three time-sessions, whereas, a very similar score performance was obtained during the middle- and late time-sessions. Highly educated parents have a positive effect on student performance. respectively (P=0.005). Conclusion: Early session has the least score performance among the three time-sessions, whereas, a very similar score performance was obtained during the middle- and late time-sessions. Highly educated parents have a positive effect on student performance.